Knowledge and barriers among Lebanese community pharmacists in pediatric antibiotic dosing: a cross-sectional study - Akiki, Stephanie; Saab, Joyce; Safwan, Jihan; Chahine, Bahia; Rahal, Mohamad (Frontiers in Pediatrics, 2025)
BackgroundThe accurate dosing of antibiotics in pediatric patients is critically important in Lebanon due to the high prevalence of antibiotic misuse, widespread over-the-counter access without prescriptions, and limited healthcare access for a significant portion of the population. The study aimed to assess the knowledge of Lebanese community pharmacists regarding proper antibiotic dosing in pediatric patients, identify the factors that influence their knowledge, and explore the barriers that lead to improper dosing of antibiotics.MethodsA cross-sectional questionnaire-based study was conducted where 309 community pharmacists were recruited through social media platforms to complete a self-administered questionnaire. The survey consisted of seven sections, including demographic characteristics, case scenarios, and barriers related questions about pediatric antibiotic dosing. Chi-square test assessed associations; variables with p ≤ 0.2 were included in the logistic regression. Significance was set at P ≤ 0.05.Results84.1% of community pharmacists had adequate knowledge about antibiotics dosing in pediatric patients. Monthly income exceeding 5,000,001 Lebanese Pounds (LBP) (CI: 3.135–12.434, P = 0) and working more than 8 h per day (CI: 0.112–0.938, P = 0.038) were significantly associated with knowledge levels. Pharmacists were mostly knowledgeable regarding the dosing of amoxicillin-clavulanate in acute otitis media with the highest correct response rate (98%), while the case of trimethoprim-sulfamethoxazole dosing in urinary tract infection had the lowest correct response rate (75.1%). Lack of scientific knowledge was reported as the most common barrier causing dosing errors.ConclusionsThe study concluded that most community pharmacists have appropriate knowledge about the correct antibiotic dosage for pediatric patients. However, there are still barriers that need to be addressed to improve pharmacists' practice and reduce dosing errors which can lead to serious consequences such as therapeutic failure, antibiotic resistance, toxicity and side effects, altered gut microbiota, increased healthcare burden, and negative impacts on a child's growth and development. The authorities should consider implementing more effective platforms and targeted educational programs to keep pharmacists informed and up-to-date, which could enhance the healthcare sector.